Fluid flow and acoustic absorption in porous metallic structures using numerical simulation and experimentation - Otaru, Abdulrazak Jinadu (2018)
The need to cut down vibration and minimize back pressure wave in a loudspeaker has led to the choice of artificially-made metallic foam structure due to its important low weight, recyclable, stiffness, high surface area, and longer active product life for money. Commercially available highly porous metallic structures are known to be poor sound absorber and there is a possibility that if they can be made by interacting with the shapes and structural properties of this material, they could make useful. Currently available poroacoustic models needed to describe the sound absorption behaviour of porous materials point out the permeability of this structure as the key parameter driving this behaviour. Knowing this parameter through experimentation or prediction is imperative to the design of material with novel attributes for this process.